A comparation: Implementation lean construction between design & build and design bid build government project in Indonesia - Sari, Endah Murtiana; Bigwanto, Arviga; Wibowo, Mochamad Agung; Thohirin, Antho; Al Fath, Ade Achmad (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of implementing lean construction in construction projects is to reduce waste and increase project productivity, ensuring that the project achieves high performance sustainably. Projects that exhibit high performance in terms of cost, quality, time, safety, and environment are the aspirations of all parties involved, including owners, contractors, and other entities. This study aims to provide a comparison of lean construction implementation using Key Performance Indicators (KPIs) developed based on a matrix, to evaluate the performance between Design & Build (DB) and Design Bid Build (DBB) projects in Indonesian government projects. Through questionnaires and in-depth interviews distributed to DB and DBB project participants in government projects, this study reveals different patterns in the implementation of lean construction between DB and DBB projects. The results of this comparison indicate differences in interaction from the initiation phase, which affects the design and implementation phases of the project. Ultimately, distinct quadrants can be described as the outcomes of lean construction implementation in government projects between DB and DBB. This study is beneficial for all parties seeking to develop lean construction in projects to achieve sustainable project performance by continuously reducing waste and increasing productivity.